Factors associated with physical activity promotion by allied and other non-medical health professionals: A systematic review. Issue 10 (October 2018) - Crisford, Paul; Winzenberg, Tania; Venn, Alison; Schultz, Martin; Aitken, Dawn; Cleland, Verity
Highlights: 30 studies identified, covering 9 professions, mostly nurses and physiotherapists. Many factors were shown to influence PA promotion but not remuneration. Key factors included self-efficacy, PA beliefs, assessment and promotion training. There is substantial opportunity for non-medical professionals to promote PA. There is an absence of studies from many health professions and a lack of RCTs. Abstract: Objective: To identify factors associated with non-medical health professionals' engagement in physical activity (PA) promotion. Methods: Five electronic databases were searched for studies including practising health professionals (excluding medical doctors), a PA promotion practice measure, a test of association between potential influencing factors and PA promotion practice, and written in English. Two researchers independently screened studies and extracted data. Extracted data were synthesized in a tabular format with a narrative summary (thematic analysis). Results: Thirty studies involving 7734 non-medical health professionals were included. Self-efficacy in PA promotion, positive beliefs in the benefits of PA, assessing patients' PA, and PA promotion training were the main factors associated with engaging in PA promotion. Lack of remuneration was not associated. Common study limitations included a lack of information on non-responders, data collection by survey only and limited reliability or validity testing of measurements. Conclusions: There are common factors influencing PA promotion, but the absence of studies from some health professions, limitations related to study measures, and the lack of randomised controlled intervention trials highlights the need for further research. Practice Implications: The factors identified may prove useful for guiding the development of strategies to encourage greater engagement in PA promotion by health professionals.